Analisis Materi Pokok Matematika dalam Membangun Literasi Numerasi Siswa Kelas III Sekolah Dasar - Lestari, Shindy; Savira, Liza; Hajjina, Cut Yuni Nurul (Musamus Journal of Primary Education, 2022)
Mathematics learning in elementary schools must innovate to develop numerical literacy as a 21st-century skill. This study aims to develop teaching materials oriented toward numerical literacy to help third-grade elementary school students apply mathematical concepts to solve real-life problems. This research employs a qualitative method with a content analysis design on integrative thematic textbooks. The findings indicate that effective learning in developing numerical literacy requires both intradisciplinary and interdisciplinary approaches. These approaches enable students to engage in Higher Order Thinking Skills (HOTs) through mathematics material presented contextually, transitioning from concrete to abstract. Thus, the implemented learning strategies can equip elementary school students with numerical literacy from an early age, which is essential for adapting to the challenges of modern developments.